Thrombotic Thrombocytopenic Purpura after COVID-19 Vaccination: A Case Report - Hasselbach, Lisa; Voß, Andreas (Archives of Clinical and Biomedical Research, 2021)
We present the, to our best knowledge, first case of a 25-year old female who developed thrombotic thrombocytopenic purpura after receiving the COVID-19 vaccination with Spikevax? (COVID-19 Vaccine Moderna). She presented with petechia, acute kidney injury and neurological symptoms. After treatment with plasma exchange, Caplacizumab and Prednisolone she first recovered but relapsed after early discontinuation of Caplacizumab. Acquired thrombotic thrombocytopenic purpura after SARS-CoV2 vaccination is a rare phenomenon that has now been seen in all of the four vaccines currently approved by the European Medicines Agency.